УЧАСТИЕ И КЛЮЧЕВЫЕ АСПЕКТЫ ДЕЯТЕЛЬНОСТИ УЗБЕКИСТАНА В МЕЖПАРЛАМЕНТСКОЙ АССАМБЛЕЕ СНГ - Азизов И. Р. (TARIXIY TADQIQOTLAR, 2024)
The article examines the interaction of the Oliy Majlis of the Republic of Uzbekistan with the Interparliamentary Assembly of the Commonwealth of Independent States (IPA CIS) since the country’s accession to the CIS in 1991. The dynamics of cooperation, key achievements and challenges are examined. Particular attention is paid to Uzbekistan’s initiatives within the IPA CIS, including the development of model legislation, strengthening interparliamentary ties and promoting regional security. In addition, the impact of cooperation on domestic reforms and the international image of Uzbekistan is analyzed, and the potential of the IPA CIS as an important platform for interstate cooperation is highlighted.